Comprehensive targeted next‐generation sequencing approach in the molecular diagnosis of gastrointestinal stromal tumor. Issue 4 (14th December 2020) - Vanden Bempt, Isabelle; Vander Borght, Sara; Sciot, Raf; Spans, Lien; Claerhout, Sofie; Brems, Hilde; Lehnert, Stefan; Dehaspe, Luc; Fransis, Sabine; Neuville, Bart; Topal, Baki; Schöffski, Patrick; et al.
Abstract: Mutational analysis guides therapeutic decision making in patients with advanced‐stage gastrointestinal stromal tumors (GISTs). We evaluated three targeted next‐generation sequencing (NGS) assays, consecutively used over 4 years in our laboratory for mutational analysis of 162 primary GISTs: Agilent GIST MASTR, Illumina TruSight 26 and an in‐house developed 96 gene panels. In addition, we investigated the feasibility of a more comprehensive approach by adding targeted RNA sequencing (Archer FusionPlex, 11 genes) in an attempt to reduce the number of Wild Type GISTs. We found KIT or PDGFRA mutations in 149 out of 162 GISTs (92.0%). Challenging KIT exon 11 alterations were initially missed by different assays in seven GISTs and typically represented deletions at the KIT intron 10‐exon 11 boundary or large insertions/deletions (>24 base pairs). Comprehensive analysis led to the additional identification of driver alterations in 8/162 GISTs (4.9%): apart from BRAF and SDHA mutations (one case each), we found five GISTs harboring somatic neurofibromatosis type 1 ( NF1 ) alterations (3.1%) and one case with an in‐frame TRIM4‐BRAF fusion not reported in GIST before. Eventually, no driver alteration was found in two out of 162 GISTs (1.2%) and three samples (1.9%) failed analysis. Our study shows that a comprehensive targeted NGS approach is feasible for routine mutational analysis of GIST, thereby substantially reducing the number of Wild Type GISTs, and highlights the need to optimize assays for challenging KIT exon 11 alterations.